Pengawasan Pemerintah Daerah Terhadap Tempat Penjualan Rokok - Karels, Alessandro Imanuel Caesarea Karels; Pattinasarany, Yohanes; Singkery, Michael Rolando (PATTIMURA Law Study Review, 2025)
Supervision of cigarette sales is one form of implementation of health policies in order to protect the public from the negative impacts of tobacco consumption. The Indonesian Constitution has emphasized that health is a human right as stated in Article 28H of the 1945 Constitution of the Republic of Indonesia. In addition, further regulations regarding the security of tobacco products have been outlined in Law Number 17 of 2023 concerning Health and Government Regulation Number 109 of 2012 and Government Regulation Number 28 of 2024. However, in reality, the supervision carried out by the Ambon City government has not been running well, the circulation of cigarette sales is increasing in Ambon City with the presence of more and more business actors, this indicates that the government's supervision has not been running optimally. The research used by the author is empirical juridical research. Procedures for collecting legal materials by conducting research in the form of interviews and observations as well as literature studies on legal materials, namely primary legal materials and secondary legal materials. Then the legal materials that have been obtained are analyzed descriptively-qualitatively. The results obtained are that the implementation of supervision by the regional government of cigarette sales places in Ambon City is still not running optimally. Although regulations have regulated cigarette control, weak implementation and lack of supervision have caused the regulations to be ineffective. Various violations of the provisions that have been set continue to occur without any significant action from the regional government so that the Legal Consequences of the Regional Government Not Supervising Cigarette Sales Places in Ambon City, increasing numbers of novice smokers, and decreasing the effectiveness of tobacco control policies in Ambon City.